Space Syntax Analysis On Level Of Security And Privacy Of Road Space. Case Study: Campus Area Of Universitas Gadjah Mada, Yogyakarta - Wafirul Aqli (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
The road space is not solely reserved for the public interest. In some examples can also be used exclusively for the residents of a region that have been designed from the beginning or through some post-occupancy adjustments. In the case of the campus of Gadjah Mada University (UGM) area, there are road spaces that become public facilities that pushing the campus authority to create access modifications (by closing or fencing) for the security and/or privacy purposes. How much the level of security and privacy that is obtained, in this paper were analyzed using space syntax. Through its ability to analyze the quality of space connectedness, space syntax can be used to measure the level of security and privacy refers to a benchmark proposed by Reis (2003) uses the value of the integration space. Integration of road space that is worth the low/weak (RA and RRA = 1 or more) has a low level of security but more private. While the high-value/strong integration (RA close to 0 and RRA = 0.4 to 0.6) have a high level of security but less privacy. Through the obtained analysis; a large enough degree of privacy is achieved, especially in the area of Central Office/Rectorate Building and surrounding areas, however, it become unsafe due to the activity-deserted road space situation and lack of supervision.